Juvenile Nasopharyngeal Angiofibroma - Ibrahim Irsan Nasution; Ajeng Dyah Ayu WP (Jurnal Ilmu Kedokteran, 2020)
Juvenile nasopharyngeal angiofibroma (JNA) is a rare benign tumour affecting mostly adolescent and can be malignant because it’s aggressive, destructive, spread locally and often extends to the skull. The exact cause of JNA is unknown. JNA originates from the pterygopalatine fossa at the aperture of the pterygoid canal. Clinical symptoms include nasal obtruction, epistaxis and headaches. The diagnosis is based on anamnesia, physical and radiological examination. CT scan and MRI are the main modalities in detecting and determining tumour stage.